COMPETENCY-BASED TRAINING IN HYDROLOGICAL EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Hydrology is an interdisciplinary science, incorporating aspects of many Earth Sciences. Key hydrological tasks such as floods prediction, quantitative and qualitative assessment of water resources and the environmental status of water bodies become increasingly important and challenging. Latest advances in scientific and technological developments require update training. The World Meteorological Organization (WMO) encourages increasing capacity of its Training Centres to address the rapidly developing demand for improved services. However, adequate education is generally not yet available. Implementation of competency-based training is needed, including active learning approaches. The paper presents international experiences and results of the use of project-based and flipped learning while teaching hydrological curriculum at Russian State Hydrometeorological University, Saint Petersburg. Some pros and cons of these approaches and difficulties of their implementation are discussed. Usually, students improve both their competence to work independently and solve problems collaboratively. Tackling near real issues and dealing with case studies get them more engaged in educational process and enhance practical outcomes. The feedback from the students and exam results have proved the efficiency of these approaches.